EFFECTS OF PRICE AND PRODUCT QUALITY ON PURCHASE DECISIONS - Nida Nafida; Rini Mardikawanty; Nur Haris Ependi (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
This study aimed to determine the extent to which Price and Product Quality influence Purchase Decisions for clothing products in the Shopee E-commerce Marketplace among students of Politeknik LP3I Jakarta, Cimone Campus. This research utilized a quantitative approach. Data were collected through questionnaires and processed using SPSS version 25. The population consisted of 100 students of Politeknik LP3I Jakarta, Cimone Campus, who had purchased clothing products through the Shopee E-commerce Marketplace in 2025. The sample comprised 80 respondents selected using purposive sampling techniques. Data analysis was conducted using multiple linear regression analysis. The findings indicated that Price partially influenced Purchase Decisions for clothing products in the Shopee E-commerce Marketplace, as evidenced by a t-statistic value of 2.569 and a significance value of 0.012. Product Quality also partially influenced Purchase Decisions, as demonstrated by a t-statistic value of 2.245 and a significance value of 0.028. Furthermore, the simultaneous test results revealed that Price and Product Quality jointly influenced Purchase Decisions, as indicated by an F-statistic value of 11.929 and a significance value of 0.000. The coefficient of determination was 0.237, indicating that Purchase Decisions were explained by the variables of Price and Product Quality by 23.7%, while the remaining 76.3% was influenced by other variables outside the scope of this study.